Do short-term, reduced-volume methods accurately reflect chronic toxic effects in the cladoceran Ceriodaphnia dubia? A study with the reference toxicant hexavalent chromium - Martínez-Jerónimo, Fernando; Martínez-Jerónimo, Laura (Frontiers in Environmental Science, 2023)
Cladocerans are frequently used as test organisms in aquatic toxicology studies. For practical reasons (bioethical and economic), efforts are currently made in search of alternative animal models and in defining short-lasting test methods that will allow reliable evaluation of the chronic effect of chemical contaminants. The use of small-sized invertebrates, like the Ceriodaphnia dubia cladoceran, represents a good option and has been included in diverse testing protocols; however, the use of reduced volumes and shortened exposure times, as well as higher temperatures to accelerate their development could influence the results and lead to imprecise conclusions. The present study aimed to evaluate the effects of different test volumes, temperature, and exposure time on the toxicity of hexavalent chrome in C. dubia. In acute and chronic assays, three test volumes (5, 15, and 25 mL) were used. Once the LC50 was determined, four sublethal concentrations (0.01, 0.02, 0.04, and 0.08 mg L−1) of Cr(VI) were applied daily to each of the three test volumes for 21 days, evaluating the progeny and survival of adults. The LC50 values did not differ at 20°C, but at 25°C they were significantly lower in 5 mL. The chronic toxic effects varied depending on the test volume and exposure time. Significant effects were observed on day 7 of exposure (corresponding to the third reproduction) in the accumulated progeny only in the volume of 5 mL. Based on the aforementioned, it is necessary to revise whether the short-term and small-scale methods are not underestimating the detection of chronic effects.